Cardiovascular risk of energy drinks: Caffeine and taurine facilitate ventricular arrhythmias in a sensitive whole‐heart model. (27th March 2022) - Ellermann, Christian; Hakenes, Tamara; Wolfes, Julian; Wegner, Felix K.; Willy, Kevin; Leitz, Patrick; Rath, Benjamin; Eckardt, Lars; Frommeyer, Gerrit
Abstract: Background: Several case reports have suggested an increased risk of sudden cardiac death due to energy drinks. Therefore, the purpose of this study was to assess acute electrophysiologic effects of caffeine and taurine, two of the main ingredients of energy drinks, in an experimental whole‐heart model. Methods and Results: Twenty‐five rabbit hearts were excised, retrogradely perfused, and assigned to two groups. Hearts were perfused with caffeine (2, 10, and 50 µM) or taurine (2, 10, and 50 µM) after generating baseline data. Eight monophasic action potentials and electrocardiography recordings showed a significant abbreviation of action potential duration (APD90 ), QT interval, and effective refractory periods (ERP) after caffeine treatment. With taurine, cardiac repolarization duration and ERP were significantly shortened. A ventricular vulnerability was assessed by a predefined pacing protocol. With caffeine, we observed a trend towards more ventricular arrhythmias in a dose‐dependent manner. After treatment with taurine, significantly more episodes of ventricular arrhythmias occurred. Conclusion: In this experimental whole‐heart study, treatment with caffeine and taurine provoked ventricular arrhythmias. The underlying mechanism was an abbreviation of cardiac repolarizations and effective refractory periods that may facilitate re‐entry and thereby provokes arrhythmias. These findings help to understand the potentially hazardous and fatal outcomes after intoxication with energy drinks.